Do Islamic Ethics Influence Consumers' Reaction to Advertising Messages of Certain Foods? Tracking Consumers' Reaction Using fMRI Technology. Issue 5 (20th October 2022) - Al-Kwifi, Osama Sam; Koku, Paul Sergius; Abu Farha, Allam K.; Al Halbadi, Salem Mohamed
Abstract: Ethics have a significant influence on business practices and consumption behavior. This influence is increasing as evidenced in the growing global demand for ethical products, particularly Halal products. We, in this study, use the functional Magnetic Resonance Imaging (fMRI) technique to investigate consumers' reaction to advertising messages of ethical products, specifically Halal products. We used a blocked design approach to measure brain activities when consumers are presented with images of Halal and non-Halal food products. The level of brain activation in the ventromedial prefrontal cortex (vmPFC) increased significantly for Muslim participants (9.51) compared to non-Muslims participants (2.94), when both groups were presented with Halal images. The elevated activity in the vmPFC of Muslim consumers in this study supports the hypothesis that ethical obligations significantly impact the consumption behavior of Muslims. Furthermore, the fact that the reaction of Muslims to images of Halal foods results in elevated activities in the vmPFC suggests that their reaction is cerebral instead of emotional. The results of this study suggest that, to improve their chances of success in Muslim markets, marketing managers of multinational companies should use advertising messages that 1) highlight the ethical dimensions of their offerings, and 2) use cognitive instead emotional appeals.